The Eleventh Winnipeg Show. (Winnipeg : Winnipeg Art Gallery, 1968)
Molinari, Guido ; Tascona, Tony ; Burton, Dennis ; Nolté, Gunter ; Sures, Jack ; Boning, Jan ; Dmytruk, Ihor ; Knowles, Dorothy ; Schmidt, Marianna ; Smith, Gordon A. ; Urquhart, Tony ; etc.
The Eleventh Winnipeg Show, Winnipeg Art Gallery, Winnipeg, October 30 - November 24, 1968
Engels
kunstcatalogus